2012
DOI: 10.1016/j.siny.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of the upper and lower genital tract

Abstract: Summary Our understanding of the bacterial species inhabiting the female genital tract has been limited primarily by our ability to detect them. Early investigations using microscopy and culture-based techniques identified lactobacilli as the predominant members of the vaginal microbiota and suggested that these organisms might serve a protective function at the mucosal surface. Improvements in cultivation techniques and the development of molecular-based detection strategies validated these early findings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 94 publications
0
46
0
4
Order By: Relevance
“…Analysis of the healthy female genital tract has proved to be a challenge since present results suggest there is both significant microbe diversity and site specificity [49].…”
Section: Figurementioning
confidence: 87%
“…Analysis of the healthy female genital tract has proved to be a challenge since present results suggest there is both significant microbe diversity and site specificity [49].…”
Section: Figurementioning
confidence: 87%
“…Comprehensive studies on healthy human vaginal microbiome have identified Lactobacillus spp. to be the dominant bacterial species by both culture-dependent and -independent methods [110][111][112][113]. Although absolute numbers vary, due to different endogenous and exogenous conditions (age, lifestyle, pregnancy, hormone levels, etc.…”
Section: A Role For the Microbiome?mentioning
confidence: 99%
“…However, the resident bacteria of the reproductive tract also play an important role, influencing the acidity of the cervicovaginal fluid (CVD), inflammatory and immune reactions, and reproductive success in women (Aldunate et al, ; Eloe & Rasko, ). For those who study nonhuman primates, it is of further interest that there is a very dramatic difference between the vaginal bacteria found in female monkeys and apes as compared to the microbial profiles of healthy women (Rampersaud, Tanis, & Ratner, ; Stumpf et al, ). In contrast to the typical predominance of just one genus, Lactobacilli , in women (Ravel et al, ), a more diverse polymicrobial community structure is commonly found in the lower reproductive tract of all nonhuman primates that have been studied (Yildirim et al, ).…”
Section: Introductionmentioning
confidence: 99%